2005
DOI: 10.2486/indhealth.43.193
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Concentration of Urinary 6-sulphatoxymelatonin during a Week of Simulated Night Work

Abstract: The aim of the study was to examine the adaptation of participants to a common night work schedule using urinary 6-sulphatoxymelatonin (aMT6s) concentration as the circadian phase marker. Fifteen adults (7 male, 8 female, age = 21.9 yr) spent nine consecutive nights in the laboratory, including: (i) adaptation sleep, (ii) baseline sleep, and (iii) seven simulated night shifts (23:00-07:00 h) followed by daytime sleep. During the baseline and daytime sleeps, participants collected urine samples which were subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…More recently, Roach et al (120) conducted a simulated nightshift work study in which participants ''worked'' 7 consecutive 8-h shifts and reported a mean phase delay of 5.5 h by night 7 using salivary melatonin measurements to detect the phase shift. A later study by this same investigative team reported similar results using urinary aMT6s levels to assess phase delay (121).…”
Section: Melatonin As a Biomarker Of Circadian Dysfunctionsupporting
confidence: 57%
“…More recently, Roach et al (120) conducted a simulated nightshift work study in which participants ''worked'' 7 consecutive 8-h shifts and reported a mean phase delay of 5.5 h by night 7 using salivary melatonin measurements to detect the phase shift. A later study by this same investigative team reported similar results using urinary aMT6s levels to assess phase delay (121).…”
Section: Melatonin As a Biomarker Of Circadian Dysfunctionsupporting
confidence: 57%
“…Normally, phase delay happens after multiple night in a row, in which the central sleep-wake cycle adapted to being awake at night and lead to delay in the time of maximum secretion of urinary 6-sulphatoxymelatonin (29). Thus, the increased level of urinary 6-sulphatoxymelatonin at the end of the fifth nightshift may be explained by the effect of phase delay, when the peak of nocturnal melatonin secretion was captured, a hypothesis that accords with previous studies that have reported that phase delay (adaptation) seldom happens during the first three days of night-shift work (29,34). Moreover, the timing of peak melatonin production can vary from one individual to another, as demonstrated in a previous study that found evidence for a large variation between individuals (35).…”
Section: Resultssupporting
confidence: 78%
“…For example, they do not have a corresponding increase in the excretion of 6-sulfatoxymelatonin during the following sleep period, which is linked to more symptoms of sleep disturbances and fatigue (Burch et al, 2005). This effect, however, may wear off: Roach et al (2005) showed that the urinary excretion of 6-sulfatoxymelatonin was reduced during the first three daytime sleeps in a simulated night work schedule, but there was no significant reduction in the excretion of 6-sulfatoxymelatonin in the urine thereafter, indicating a shift in the circadian rhythm.…”
Section: Discussionmentioning
confidence: 97%